Project on Human Development in Chicago Neighborhoods (PHDCN): Extended Family Health, Wave 3, 2000-2002 - Earls, Felton J. ([Verlag nicht ermittelbar], 2007)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One such measure was the Extended Family Health instrument. It was administered to subjects' primary caregivers in Cohorts 0, 3, 6, 9, 12, and 15 and obtained information about the physical health, mental health, criminal history, and drug use history of anyone who ever lived in the same household as the subject for any period of time.